2011
DOI: 10.1016/j.biomaterials.2010.09.053
|View full text |Cite
|
Sign up to set email alerts
|

Delivery of rosiglitazone from an injectable triple interpenetrating network hydrogel composed of naturally derived materials

Abstract: An in situ gelable and biodegradable triple-interpenetrating network (3XN) hydrogel, completely devoid of potentially cytotoxic extraneous small molecule crosslinkers, is formulated from partially oxidized dextran (Odex), teleostean and N-carboxyethyl chitosan (CEC). Both the rheological profile and mechanical strength of the 3XN hydrogel approximate the combined characteristics of the three individual hydrogels composed of the binary partial formulations (i.e., Odex/CEC, Odex/teleostean, and CEC/teleostean). … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
43
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 41 publications
(43 citation statements)
references
References 40 publications
0
43
0
Order By: Relevance
“…Sham samples (n ¼ 7) received an injection of the PBS, while the implant group (n ¼ 7) received an injection of the hydrogel implant. The hydrogel implant was created by mixing aqueous solutions of 20% teleostean, 3% N-carboxyethyl chitosan, and 7.5% oxidized dextran were at a ratio of 1:1:2 [15]. Toluidine blue was mixed in the aqueous solution of teleostean before mixing the hydrogel components to permit visualization of the implant.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Sham samples (n ¼ 7) received an injection of the PBS, while the implant group (n ¼ 7) received an injection of the hydrogel implant. The hydrogel implant was created by mixing aqueous solutions of 20% teleostean, 3% N-carboxyethyl chitosan, and 7.5% oxidized dextran were at a ratio of 1:1:2 [15]. Toluidine blue was mixed in the aqueous solution of teleostean before mixing the hydrogel components to permit visualization of the implant.…”
Section: Methodsmentioning
confidence: 99%
“…In this study, we will be evaluating an in situ gelable, triple-interpenetrating-network hydrogel nucleus replacement. The gel is composed of n-carboxyethyl chitosan, oxidized dextran, and teleostean and is well suited as a nucleus replacement in part because after mixing it solidifies rapidly at body temperature and demonstrates increased resistance to biodegradation relative to single-network hydrogels [15]. It has also recently been demonstrated that the gel maintains cell viability, promotes proliferation, and has mechanical properties similar to native human nucleus pulposus [16].…”
Section: Introductionmentioning
confidence: 99%
“…Previous work has shown that the combination of these materials produces a hydrogel with increased resistance to biodegradation relative to single-network hydrogels, and improved mechanical strength as demonstrated by rheological characterization. 19 Previous work has also shown that in vivo subcutaneous injection of the hydrogel in mice does not induce a significant inflammatory response or evidence of tissue necrosis, suggesting that the hydrogel and its degradation by-products have minimal cytoxicity concerns. 19 The overall objective of this study was to investigate the potential of this hydrogel for NP regeneration.…”
Section: Introductionmentioning
confidence: 99%
“…This hydrogel is comprised of three naturally derived materials: N-carboxyethyl chitosan, oxidized dextran, and teleostean. 19 Upon mixing, these components rapidly solidify at physiological temperatures in the absence of any extraneous crosslinking agents. Previous work has shown that the combination of these materials produces a hydrogel with increased resistance to biodegradation relative to single-network hydrogels, and improved mechanical strength as demonstrated by rheological characterization.…”
Section: Introductionmentioning
confidence: 99%
“…Further, an in-situ injectable and biodegradable triple-interpenetrating network (3XN) hydrogel, was developed in order to deliver rosiglitazone which was comprised from dextran, teleostean and N-carboxyethyl chitosan. The dissolution ability was reported as sustained for the model drug 63 .…”
Section: Pharmaceutical Formulations For the Delivery Of Thiazolidinementioning
confidence: 99%